2018
DOI: 10.1017/s0022215118000609
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cochlear implant bed preparation and fixation technique on the revision cochlear implantation rate

Abstract: Accurate fixation of the cochlear implant receiver/stimulator is crucial for successful cochlear implantation. As the bone recess with suture fixation technique is associated with a lower revision rate and a similar complication rate as the subperiosteal tight pocket technique, it should be the preferred fixation technique for cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…showed that the bone recess with suture receiver/stimulator fixation technique was associated with a lower revision rate than the subperiosteal pocket technique. 11 Based on our experience, modified minimal access surgery, as described by Sennaroglu et al ., 12 allows the surgeon to perform the time-consuming work of drilling holes for tie-down sutures using a smaller post-auricular incision than is possible with other surgical methods. The present findings seem to support Shelton and Warren's theory 13 that micro-movement of the fantail can lead to wire fatigue and fantail damage.…”
Section: Discussionmentioning
confidence: 99%
“…showed that the bone recess with suture receiver/stimulator fixation technique was associated with a lower revision rate than the subperiosteal pocket technique. 11 Based on our experience, modified minimal access surgery, as described by Sennaroglu et al ., 12 allows the surgeon to perform the time-consuming work of drilling holes for tie-down sutures using a smaller post-auricular incision than is possible with other surgical methods. The present findings seem to support Shelton and Warren's theory 13 that micro-movement of the fantail can lead to wire fatigue and fantail damage.…”
Section: Discussionmentioning
confidence: 99%
“…One study from this review reported advantages of the traditional technique in a sample of over 1,500 CI cases. (5) This study describes similar wound complication rates between the two techniques but found higher revision rates in the subperiosteal pocket technique due to IRS migration (5). Although our meta-analysis did not report a significant difference in the risk of wound complication between the two IRS fixation methods, the overall data, including unpaired samples, showed a trend toward higher rates of wound complications in the standard fixation method.…”
Section: Discussionmentioning
confidence: 61%
“…Five of these studies compared cochlear implantation with suture fixation of the IRS to cochlear implantation with a subperiosteal pocket fixation of the IRS using a paired-sample design and, thus, a meta-analysis was conducted with these studies (Fig. 3) (5,16,(23)(24)(25). While well-drilling was common among the suture fixation studies, not all studies commented on whether a well was drilled or not.…”
Section: Implant Placement/fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, these failures did not appear to cause a decline in performance, however devices with more than three electrode failures were at high risk for future device performance deterioration leading to explantation (26,30). The causes for these failures included loss of hermetic seal, fatigue fractures due to micro-movements in the electrode lead exit or the electrode lead itself (31)(32)(33)(34), or external trauma, where the latter was reportedly more common in children (32,35). In a recent revision case of robotic cochlear implantation, Morrel et al observed wire fractures at the acute turn from the mastoid surface into the drilled tunnel (36), and have suggested smoothing the edges of the tunnel at the surface of the mastoid.…”
Section: Cochlear Implantation Complicationsmentioning
confidence: 99%